Pengaruh Pemberian Minuman Vitamin C dengan VO2 Max, Pemulihan Denyut Nadi, dan Masa Pemulihan - Fandy Ong Jaya; Eka Roina Megawati (Fakultas Kedokteran, Universitas Andalas, 2022)
Vitamin C, as one of the antioxidants in energy drinks, plays an essential role in physical endurance. Modified Harvard step test is a cardiac endurance test to assess cardiac fitness based on VO2 max, heart rate recovery, and recovery period. Objectives: assessed the relationship between giving vitamin C before exercising with heart-lung fitness in the form of VO2 max, recovery of pulse rate, and recovery period. Methods: The design of this study was a pretest-posttest study with a control group of 40 male students aged 18-22 years old. One week before administrating vitamin C, the VO2 max of all subjects was measured using the modified Harvard step test. The subjects were divided into two groups, the vitamin C group, which had vitamin C drinks prior to the step test and the control group only had plain water. Results: There was no significant difference in VO2max, Heart Rate Recovery (HRR) 1 minute, HRR 2 minute, and recovery time before and after consuming vitamin C between groups with p value = 0.090, 0.181, 0.211, and 0.95, respectively (p > 0.05). This study showed that there was no difference in VO2 max before and after vitamin C consumption. Conclusion: Vitamin C drinks consumption before the step test cannot increase the VO2 max, heart rate recovery, and recovery time.Keywords: heart rate recovery, recovery time, vitamin C, VO2 max